2023
DOI: 10.3389/fbioe.2023.1128762
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on various cell sources for constructing tissue-engineered meniscus

Abstract: Injury to the meniscus is a common occurrence in the knee joint and its management remains a significant challenge in the clinic. Appropriate cell source is essential to cell-based tissue regeneration and cell therapy. Herein, three commonly used cell sources, namely, bone marrow mesenchymal stem cell (BMSC), adipose-derived stem cell (ADSC), and articular chondrocyte, were comparatively evaluated to determine their potential for engineered meniscus tissue in the absence of growth factor stimulus. Cells were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Additionally, the SSF group demonstrated the highest secretion capacity of glycosaminoglycan (GAG) on day 21 (Figure C). This result indicated that the SSF group provided the most suitable environment for ECM secretion by BMSCs, thus promoting the maturation of bone tissue structures . Furthermore, ALP activity was measured on days 7 and 14 of osteogenic induction (Figure D).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Additionally, the SSF group demonstrated the highest secretion capacity of glycosaminoglycan (GAG) on day 21 (Figure C). This result indicated that the SSF group provided the most suitable environment for ECM secretion by BMSCs, thus promoting the maturation of bone tissue structures . Furthermore, ALP activity was measured on days 7 and 14 of osteogenic induction (Figure D).…”
Section: Resultsmentioning
confidence: 77%
“…The morphology of short electrospinning SiO 2 nanofibers and scaffolds was observed by scanning electron microscopy (SEM, Phenom, Netherlands) at an accelerating voltage of 5 kV. The diameter and length of short nanofibers were measured based on SEM images using ImageJ …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this issue, many studies have explored the potential benefits of adding a significant number of cells to the scaffold. Numerous studies have examined the value of various cell types in cartilage repair, including hyaline chondrocytes [ 106 , 107 ], fibrochondrocytes [ [108] , [109] , [110] ], elastic chondrocytes [ 111 , 112 ], and diverse mesenchymal stem cells [ [113] , [114] , [115] ].…”
Section: Bionic Materialsmentioning
confidence: 99%